Hepatitis E: update and perspectives - GUȚU, Veaceslav (One Health & Risk Management, 2021)
Introduction. There are approximately 20 million cases of HVE annually worldwide, leading to approximately 3.3 million symptomatic cases of acute hepatitis E. The WHO estimates that HEV caused approximately 44,000 deaths in 2015 accounting for 3.3% of the mortality rate due to viral hepatitis.Material and methods. The study of 75 bibliographic sources was carried out. The scientific platforms EMBASE, PubMed, HINARI, data from the national libraries as well as international relevant reference data were thoroughly examined.Results. The present relevant study has highlighted important aspects of hepatitis E virus infection. Along with the improved living conditions and water quality standards, the latter being a disease-causing factor in the transmission of HEV, both the developed and developing countries are facing HEV, particularly in high-risk population groups, including people who are employed in the pork-processing industry and beneficiaries of blood transfusions.Conclusions. The countries' capacity to detect and control this infection is limited since it has not been included within the surveillance policies and programs yet. Risk factors associated with the epidemic process should be elucidated to provide and develop appropriate evidence-based measures to optimize the surveillance and control system in order to reduce the risk of contracting HEV and maintain favorable conditions for epidemiological safety.